PENYELESAIAN WANPRESTASI TERHADAP PERJANJIAN PINJAMAN DI KOPERASI UNIT DESA (KUD) SUMBER REZEKI DESA BUKIT AGUNG KECAMATAN KERINCI KANAN KABUPATEN SIAK - Mia Safitri; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Law Number 25 of 1992 concerning Cooperatives, cooperativesare the foundation for strengthening the people's economy. The purpose ofcooperatives in Article 3 of Law Number 25 of 1992 aims to promote thewelfare of members in particular and society in general and to participatein building a national economic order in order to create an advanced, justand prosperous society based on Pancasila and the 1945 Constitution.Cooperative Units Sumber Rezeki Village as a savings and loancooperative. The purpose of writing this thesis is first, to find out the factorsthat cause bad loans at KUD Sumber Rezeki Bukit Agung Village. Second,to find efforts to resolve non-performing loan defaults in the implementationof money loans at KUD Sumber Rezeki Bukit Agung Village.This type of research is sociological legal research, namely researchconducted on the identification of laws and the effectiveness of laws thatapply in society. In this case, see the implementation of the Sumber RezekiCooperative loan money agreement. The nature of the research isdescriptive which provides precise data about humans, conditions and othersymptoms.The results of this study indicate that the factors that cause bad creditto the Sumber Rezeki Village Unit Cooperative are internal factorsoriginating from creditor errors, namely the lack of accuracy in providingcredit to members and no data transparency by the old KUD Sumber Rezekimanagement on the amount owed and the amount payments paid bymembers of the cooperative as well as external factors, namely thoseoriginating from the debtor either outside the condition of the debtor himselfor because of the lack of good faith, negligence or misuse of money bymembers of the cooperative. The efforts taken to resolve defaults in KUDSumber Rezeki are by sending letters of reprimand, visiting directly to theresidence of cooperative members, finding solutions for settlement in afamily manner and the final way is to sell or confiscate cooperativemembers' credit guarantees.Keywords: Default - Bad Loans, Cooperative.